PENYULUHAN TEKNIK PRODUKSI BENIH PADI BERSERTIFIKAT SEBAGAI PENDUKUNG PERTANIAN BERKELANJUTAN DI DESA SIDODADI KECAMATAN TELUK PANDAN KABUPATEN PESAWARAN PROPINSI LAMPUNG - Muhammad Kamal; Eko Pramono; Muhammad Syamsoel Hadi; Kukuh Setiawan (Jurnal Pengabdian Fakultas Pertanian Universitas Lampung, 2026)
Abstract:Food crop farmers in Sidodadi Village, Teluk Pandan District, Pesawaran Regency, Lampung Province, who are members of the Rejotani Farmers Group, have been actively cultivating rice for a long time. However, their seed needs were met by purchasing seeds from agricultural stores or using part of their own rice harvest. This was due to the farmers' lack of knowledge about the techniques for producing quality, certified rice seeds. This extension program aimed to explain the techniques for producing quality, certified rice seeds to provide farmers with this knowledge and motivate them to produce quality, certified rice seeds in the future. The extension program was held at the Village Hall of Sidodadi Village, Teluk Pandan District, Pesawaran Regency, Lampung Province, on October 1, 2025, using lecture and discussion methods. The extension results showed that a) farmers strongly recognized the importance of quality, certified rice seeds, and b) farmers who were initially unaware (70%) and curious (30%) about the techniques for producing quality, certified rice seeds became all farmers (100%) who wanted to produce quality rice seeds themselves.